The Value of Groupwork Knowledge and Skills in Focus Group Research: A Focus Group Approach With Marginalized Teens Regarding Access to Third-Level Education. Issue 1 (15th October 2019) - Jenkinson, Hilary; Leahy, Pat; Scanlon, Margaret; Powell, Fred; Byrne, Olive
This article explores the value of applying groupwork expertise and skills in conducting focus group research. It identifies and provides an analysis of comparisons between the arenas of focus group moderation and social groupwork facilitation drawing from literature from both fields. In addition, the article discusses key skills needed by focus group moderators highlighting how these are also foundational social groupwork competencies. The article draws from the authors' experiences of designing and facilitating focus groups with teenagers as part of a 2-year research study examining the perceptions and experiences of young people from marginalized communities in relation to accessing third-level education. In light of this analysis, the authors assert that some developments in focus group research methodology have resulted in a greater degree of alignment between these two spheres and that focus group moderation is enhanced and rendered increasingly effective when groupwork skills, knowledge, and insights are employed.